2011
DOI: 10.1103/physrevd.84.122001
|View full text |Cite
|
Sign up to set email alerts
|

Tests of fundamental physics with the Gaia mission through the dynamics of minor planets

Abstract: With a launch planned in March 2013, the ESA Gaia mission will scan the whole sky several times during its operational five years. It will provide highly accurate astrometric observations of celestial bodies (at the sub-milli-arcsecond level) not exclusively beyond the Solar System, since about 250 000 asteroids will be observed. Gaia will thus give us the opportunity of performing various valuable tests of fundamental physics by assessing global parameters from the dynamics of minor planets; in this paper, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 70 publications
1
12
0
Order By: Relevance
“…In addition to gravitation tests performed by measuring the light deflection, Gaia also provides a unique opportunity to test gravitation by considering the orbital dynamics of SSO. One can estimate that about 360 000 asteroids will be regularly observed by Gaia at the sub-mas level, which will allow us to perform various valuable tests of gravitation [205,206]. In particular, realistic simulations of more than 250 000 asteroids have shown that Gaia will be able to constrain the β PPN parameter at the level of 10 −3 [205].…”
Section: Missions Ttst Jsi Jmentioning
confidence: 99%
“…In addition to gravitation tests performed by measuring the light deflection, Gaia also provides a unique opportunity to test gravitation by considering the orbital dynamics of SSO. One can estimate that about 360 000 asteroids will be regularly observed by Gaia at the sub-mas level, which will allow us to perform various valuable tests of gravitation [205,206]. In particular, realistic simulations of more than 250 000 asteroids have shown that Gaia will be able to constrain the β PPN parameter at the level of 10 −3 [205].…”
Section: Missions Ttst Jsi Jmentioning
confidence: 99%
“…Gaia's objective is to unravel the kinematical, dynamical, and chemical structure and evolution of our Galaxy, the Milky Way (e.g., Gómez et al 2010). In addition, Gaia's data will revolutionise many other areas of astronomy, e.g., stellar structure and evolution, stellar variability, double and multiple stars, solar-system bodies, extra-galactic objects, fundamental physics, and exoplanets (e.g., Pourbaix 2008;Tanga et al 2012;Mignard & Klioner 2010;Eyer et al 2011;Sozzetti 2011;Mouret 2011;Tsalmantza et al 2009;Krone-Martins et al 2013). During its five-year lifetime, Gaia will survey the full sky and repeatedly observe the brightest 1000 million objects, down to 20th magnitude (e.g., de Bruijne et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously with the equations of motion, we integrate the variational equations to obtain the partial derivatives of the observables with respect to all the estimated parameters, i.e. six initial conditions for each SSO and global parameters like the Sun J 2 and the parameters characterizing the gravitational theory (for a detailed presentation of the method, see Hestroffer et al (2010), Mouret (2011) and Hees et al (2015)). Our sensitivity analysis is based on the Fisher information matrix (or covariance matrix) which gives an estimate of the uncertainty for each parameter as well as correlation coefficients.…”
Section: Methodsmentioning
confidence: 99%